Main causes of civilian vulnerability in a non- international armed conflict: An appraisal of the legal factors - Hamid, Abdul Ghafur@Khin Maung Sein (Leena and Luna International, Oyama, Japan, 2013)
There may be legal as well as non-legal factors that are the main causes of the civilian harm in a non-international armed conflict. In view of the lessons taken from civil wars that occurred around the world, the report of the UN Secretary General, and cases decided by international tribunals, the paper identifies the legal factors that contribute to the vulnerability of civilians in a civil war situation and examines each and every factor in search of possible solution or amelioration.